Age and Sex Variation in the Duration of Action and Corneal Touch Threshold (CTT) following Instillation of 0.5% Topical Ophthalmic Proparacaine and Tetracaine Hydrochlorides - Samuel Kyei; Nana Yaw Abaka Dadzie; Ebenezer Zaabaar; Kwasi Antwi Asamoah Dwomoh; Kofi Asiedu (Journal of Ophthalmology)
Purpose. We investigated the effect of age and sex on corneal touch threshold (CTT) and duration of action following administration of 0.5% topical ophthalmic proparacaine and tetracaine hydrochlorides. Methods. A prospective, randomized, subject-masked, crossover study design was used. Two hundred and forty human volunteers were enrolled in the study. Corneal touch threshold (CTT) was determined using a Cochet-Bonnet esthesiometer. CTT was measured every 15 seconds for the first 1-minute and at 5-minute intervals subsequently for a period of 40 minutes after the application of each anesthetic. CTT and duration of action of the ophthalmic solutions were tested for statistical significance using repeated measures ANOVA. Results. The total duration of effect was 20 minutes for females and 25 minutes for males for both anesthetics. The total duration of the effect of both solutions decreased with increasing age; however, elderly participants had the longest duration (5 minutes) of the maximal effect (minimum CTT) of the two ophthalmic preparations. There was a significant influence of sex, F (2.39, 569.65) = 2.86, p=0.04; F (3.48, 828.19) = 4.41, p=0.003, and age, F (4.78, 566.18) = 8.97, p<0.001; F (7.19, 852.56) = 20.55, p<0.001 on CTT following application of proparacaine hydrochloride and tetracaine hydrochloride, respectively. Conclusion. CTT and duration of anesthetic effect after instillation of 1 drop of 0.5% proparacaine hydrochloride and 0.5% tetracaine hydrochloride vary based on sex and age.